How women address their spouses: a current trend in pronoun usage - Mansor, Nor Shahila (Universidad de Chile, 2019)
This study aims to investigate the choice of address terms by Malay women from different social status and discusses its sociolinguistic implications in the present society of Malaysia. It scrutinises the different patterns of address terms used by Malay women in addressing their spouses in three specific contexts; when they are alone, in the presence of others and in the formal settings namely workplaces and meetings. The study employs a descriptive qualitative research approach. However, there are some percentages used to support the findings. The choices of address forms were gathered through a social class questionnaire answered by 97 female participants stratified to upper-middle, middle and lower-middle classes. The findings suggest that among Malay women in the upper-middle class, the preferred address terms for their husbands is the English second person singular “you”. This choice is clearly influenced by the prestige received by the English language in Malaysia. The terms of endearment become the second opted terms of address in addressing the significant others among women in the upper-middle class. Meanwhile, the majority of the participants stratified in middle and lower-middle social classes revealed a preference for using kinship terms. Sociolinguistically, the kinship terms use among spouses in Malay culture flourish the intimacy, closeness and affection, and a high level of respect toward the addressee. The results of this study will redound to the benefit of linguistic communities in particular sociolinguists and Malay language learners by providing an understanding of the current trend in pronoun usage among women in the Malay culture.